Quality enhancement of plastics recycled by incorporating lubricant additives. - Hashim, Shahrir; Rahmat, Abdul Razak (1995)

(untitled)
This paper discusses the method to enhance the quality of recycled plastics. The material used is High Density Polyethlylene (HDPE) by incorporating Calcium Stearate as an additive. Results obtained suggested that the lubricant additive has improved the physical property of the recycled plastics. Detailed discussion of the study is available in the attached article.